The Effects of Brand Ambassador, Digital Marketing, and Instagram Use on Brand Trust: A Case Study of Scarlett Whitening Product - Kumba Digdowiseiso; Rahayu Lestari; Beladdina An’nisa (Budapest International Research and Critics University, 2021)
This study aims to prove the effects of brand ambassadors, digital marketing, and Instagram use on brand trust at Scarlett Whitening products. We utilized consumers of Scarlett Whitening products in South Jakarta that were actively using Instagram, where the age of 18-38 years constituted generation Y and generation Z. This research used a accidental sampling technique and based on the chosen criteria, the number of samples used in this study were about 96 consumers. The analytical technique used in this study was Multiple Linear Regression with the assistance of MINITAB 15 software program. The results showed that brand ambassadors, digital marketing, and Instagram use affected brand trust in Scarlett Whitening products.